The predictive value of CTSI scoring system in non-operative management of patients with splenic blunt trauma: The experience of a level 1 trauma center - Ali Barah (14777533) (2023)
Background The spleen is one of the most injured organs following blunt abdominal trauma. The management options can be either operative or non-operative management (NOM) with either conservative management or splenic artery embolization. The implementation of CT in emergency departments allowed the use of CT imaging as a primary screening tool in early decision-making. Consecutively, new splenic injury scoring systems, such as the CT severity index (CTSI) reported was established. Aim The main aim of this study is to evaluate the effect of the implementation of CTSI scoring system on the management decision and outcomes in patients with blunt splenic trauma over 8 years in a level 1 trauma center. Methods This is a retrospective study including all adult patients with primary splenic trauma, having NOM and admitted to our hospital between 2013 and 2021. Results The analyses were conducted on ninety-nine patients. The average sample age was 32.7 ± 12.3 years old. A total of (63/99) patients had splenic parenchyma injury without splenic vascular injury. There is a statistically significant association between CTSI grade 3 injury and the development of delayed splenic vascular injury (p < 0.05). There is an association between severity of initial CTSI score and the risk of NOM/clinical failure (p = 0.02). Conclusion Our findings suggest implementing such a system in a level 1 trauma center will further improve the outcome of treatment for splenic blunt trauma. However, CTSI grade 3 is considered an increased risk of NOM failure, and further investigations are necessary to standardize its management. Other Information Published in: European Journal of Radiology Open License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ejro.2023.100525